2008
DOI: 10.1902/jop.2008.070571
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results of Guided Tissue Regeneration Therapy With Non‐Resorbable and Bioabsorbable Barriers. IV. A Case Series of Infrabony Defects After 10 Years

Abstract: CAL-V gain achieved 12 months after GTR therapy in infrabony defects using non-resorbable and bioabsorbable barriers was stable after 10 years in 12 of 16 defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 34 publications
(68 reference statements)
6
49
0
1
Order By: Relevance
“…PAL‐V was stable on average in both groups. The few studies that report on stability 10 years after GTR therapy observed moderate PAL‐V loss of <2.0 mm (Pretzl et al 2008, 2009). This is in accordance with the PAL‐V loss observed in this study 120 ± 12 months after therapy in both groups (OFD/GTR).…”
Section: Discussionmentioning
confidence: 99%
“…PAL‐V was stable on average in both groups. The few studies that report on stability 10 years after GTR therapy observed moderate PAL‐V loss of <2.0 mm (Pretzl et al 2008, 2009). This is in accordance with the PAL‐V loss observed in this study 120 ± 12 months after therapy in both groups (OFD/GTR).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term results after use of barrier membranes in the treatment of infrabony defects are available for follow‐up periods of 5 (Eickholz, Krigar, Kim, Reitmeir, & Rawlinson, ; Eickholz et al, ; Mengel, Schreiber, & Flores‐de‐Jacoby, ; Nickles et al, ; Sculean et al, ; Slotte, Asklow, & Lundgren, ) and 10 years (Cortellini, Carnevale, Sanz, & Tonetti, ; Cortellini & Tonetti, ; Pretzl, Kim, Holle, & Eickholz, ; Pretzl et al, ; Sculean et al, ). Longer follow‐ups of 20 years are only reported for a few regenerative methods (Cortellini, Buti, Pini Prato, & Tonetti, ; Pini Prato & Cortellini, ), but not for the use of bioabsorbable barrier membranes for periodontal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bone grafts combined with guided tissue regeneration can serve as a scaffold for clot formation and stabilization. 19 This clinical report describes novel techniques for adults undergoing accelerated osteogenic orthodontic treatment alone or combined with guided tissue regeneration to repair the osseous defect caused by mandibular anterior decompensation in Class III orthognathic patients. …”
mentioning
confidence: 99%